Harvesting left internal thoracic artery via clamshell incision for coronary bypass and lung transplant. Issue 10 (27th October 2020) - Haddad, Osama; Jacob, Samuel; Pham, Anthony; Sareyyupoglu, Basar; Dye, Kenneth; Pham, Si Mai
Abstract: Concomitant lung transplantation and coronary artery bypass grafting operation became more prevalent over the last decade due to the advanced age of recipients. Median sternotomy approach is traditionally used when internal thoracic artery is utilized. Here we report a technique of harvesting the left internal thoracic artery via a clamshell incision for a combined coronary artery bypass and bilateral lung transplant operation in a 71-year-old male with terminal respiratory failure and coronary artery disease.